ANALISIS HUKUM TERHADAP KEPEMILIKAN HAK ATAS TANAH YANG DIPEROLEH MELALUI PEWARISAN (StudiPutusanNomor 86/Pdt/2018/PT MDN) - Junius Nakhe (Jurnal Panah Hukum, 2022)
Inherited land is land obtained from the distribution of the inheritance of someone who has passed away to his heirs. In Article 20 paragraph (1) Number 5 of 1960 concerning the Basic Agrarian Law states